2012
DOI: 10.1371/journal.pcbi.1002636
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Genomics Field Trip Program Aimed at Secondary School Students

Abstract: With the rapid pace of advancements in biological research brought about by the application of computer science and information technology, we believe the time is right for introducing genomics and bioinformatics tools and concepts to secondary school students. Our approach has been to offer a full-day field trip in our research facility where secondary school students carry out experiments at the laboratory bench and on a laptop computer. This experience offers benefits for students, teachers, and field trip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It was first identified by individual educators who developed bioinformatics teaching materials, which were integrated into their lessons [19, 20]. Today, diverse bioinformatics-based online resources, such as educational tools [21], educational games [22], outreach programs [23–25], collaborations with researchers [26, 27], lessons and teaching modules ([28–32, 33]; e.g.) are being offered to high-school students.…”
Section: Introductionmentioning
confidence: 99%
“…It was first identified by individual educators who developed bioinformatics teaching materials, which were integrated into their lessons [19, 20]. Today, diverse bioinformatics-based online resources, such as educational tools [21], educational games [22], outreach programs [23–25], collaborations with researchers [26, 27], lessons and teaching modules ([28–32, 33]; e.g.) are being offered to high-school students.…”
Section: Introductionmentioning
confidence: 99%
“…Several university-based outreach programs have existed in the United States and overseas to promote disciplines such as agriculture (Moore & Holmes, 2003), electrical engineering (Smaill, 2010), genomics (McQueen, Wright, & Fox, 2012), natural resources (Martinez, Lindline, Petronis, & Pilotti, 2012), and physics (Gallitto, 2010;Gallitto, Agnello, & Cannas, 2011;Zeng, Cunningham, Tidrow, Smith, & Contreras, 2016). These outreach programs, despite differences in disciplines, geographic locations, logistics, and duration, succeeded in increasing student interest in STEM fields due to the following four characteristics: (a) directly immersing participating students in a university learning environment where advanced equipment is readily available, (b) involving the participating students in stimulating hands-on activities with the equipment, (c) creating ample opportunities for students to interact with professors or senior students with enthusiasm in the field, and (d) exposing participating students to valuable field knowledge.…”
Section: Existing University-based Outreach Programsmentioning
confidence: 99%
“…Fundamentally, all of these outreach programs have increased students' intrinsic value of studying a subject. However, very few programs, other than the Genomics Field Trip program at the University of British Columbia by McQueen et al (2012), included a solid component focusing on improving students' utility value by shedding light on career choices. Consequently, their survey results showed that students enjoyed learning about the various jobs related to that field.…”
Section: Existing University-based Outreach Programsmentioning
confidence: 99%
“…Gallagher et al 2011;Lewitter and Bourne 2011;McQueen et al 2012;Kovarik et al 2013;Machluf and Yarden 2013;Wood and Gebhardt 2013;Marques et al 2014;Toby and Pope 2014). Genomics and associated topics have started to appear in many official school curricula, for example in Scotland (see "Discussion", below), the Netherlands (College voor Examens 2014, p. 17) and the USA (Wefer and Sheppard 2008).…”
Section: Introductionmentioning
confidence: 99%